Analysis of the School Zoning System and its Impact on the Education System: Between Equality and Disparity - Sutadi, Sutadi; Sumirah, Dila; Lisyani, Lisyani; Agustina, Demi (PPSDP International Journal of Education, 2025)
This study aims to analyze the extent to which the school zoning system has achieved the goal of equalizing education and how this system has impacted the education gap in Indonesia. This article uses a library method that focuses on collecting and analyzing data from various written sources, both in print and digital form. This approach allows researchers to access relevant information and ideas without having to go directly to the field. Zoning can provide equal access to education by increasing student access to the nearest school, as well as increasing school participation, especially at the elementary and secondary levels. However, in its implementation, zoning has not been able to equalize the quality of facilities between schools. The zoning system also has implications for the effectiveness of learning, some schools in densely populated areas accept students beyond capacity, while schools in other areas lack students. Although the goal of zoning is to eliminate the stigma of favorite schools, the community still views schools in certain zones as better, reinforcing the gap in perception. Zoning has not fully realized social justice in education, because students from families with more resources still have advantages. Therefore, this study recommends policies to support the zoning system. The government needs to accelerate infrastructure improvements in disadvantaged schools so that the quality of education is evenly distributed. Then accelerate the improvement of teacher redistribution and training programs to ensure that all schools have quality educators. Finally, conduct periodic evaluations of the zoning system to identify and correct deficiencies in its implementation.